Oligodendroglial Argonaute protein Ago2 associates with molecules of the Mbp mRNA localization machinery and is a downstream target of Fyn kinase - Müller, Christina; Schäfer, Isabelle; Luhmann, Heiko J.; White, Robin (Frontiers in Cellular Neuroscience, 2015)
Oligodendrocytes myelinate neuronal axons in the central nervous system (CNS) facilitating rapid transmission of action potentials by saltatory conduction. Myelin Basic Protein (MBP) is an essential component of myelin and its absence results in severe hypomyelination in the CNS of rodents. Mbp mRNA is not translated immediately after exit from the nucleus in the cytoplasm, but is transported to the plasma membrane in RNA transport granules in a translationally silenced state. We have previously identified the small non-coding RNA 715 (sncRNA715) as an inhibitor of Mbp translation associated with RNA granules. Argonaute (Ago) proteins and small RNAs form the minimal core of the RNA induced silencing complex (RISC) and together recognize target mRNAs to be translationally inhibited or degraded. Recently, tyrosine phosphorylation of Ago2 was reported to be a regulator of small RNA binding. The oligodendroglial non-receptor tyrosine kinase Fyn is activated by neuronal signals and stimulates the translation of Mbp mRNA at the axon-glial contact site. Here we analyzed the expression of Ago proteins in oligodendrocytes, if they associate with Mbp mRNA transport granules and are tyrosine phosphorylated by Fyn. We show that all Ago proteins (Ago1-4) are expressed by oligodendrocytes and that Ago2 colocalizes with hnRNP A2 in granular cytoplasmic structures. Ago2 associates with hnRNP A2, Mbp mRNA, sncRNA715 and Fyn kinase and is tyrosine phosphorylated in response to Fyn activity. Our findings suggest an involvement of Ago2 in the translational regulation of Mbp. The identification of Ago proteins as Fyn targets will foster further research to understand in more molecular detail how Fyn activity regulates Mbp translation.